Criminal proceedings - Aragea, Cosmina Claudia (Eximia, 2023)
Offences that break the rules in the area of criminal law will lead to conflicts in criminal law, and to this end, the judiciary must resolve criminal proceedings. Criminal conduct can be reviewed and analysed from the perspective of substantive, substantive law, procedural law and formal law. With the adoption and promulgation of criminal law, a criminal legal relationship was formed. Defending social values and imposing certain behaviors, on the other hand are individuals. Laws or laws covered by the provisions of the Criminal Code. The state has the right to prosecute without observing the rules of criminal law, which is an important part of criminal proceedings. When committing a crime, the judicial department exercises its right to defend social values by promoting criminal behavior, so virtual laws have been substantially transformed and are becoming active, and criminal proceedings have begun to restore law and order. Criminal procedure is a right, from a procedural perspective, it is an abstraction and it is a lever to exercise this right. In criminal law governing criminal acts, the prosecution of conflicts caused by violations of criminal law is implicitly institutionalized to prosecute those who commit such acts. Criminal disputes, as a legal means of transmitting conflict reports to court, already exist in the legal norms of criminal law, but have become a specific means and can be used. The consequence of committing an unlawful act is the use (exercise) of the act. Until the moment when the illegal act is committed, the act conferred by the legal norms practically exists as a legal power of creation. From that moment on, the act can be exercised, that is, a power with real effect.